ADMINISTRATIVE EXPULSION IN RUSSIAN JUDICIAL PRACTICE: DOCTRINAL DEBATES AND LEGAL GUIDELINES FOR UZBEKISTAN (World Bulletin of Management and Law, 2025)
This article offers a theoretical and practical analysis of administrative expulsion of foreign nationals, focusing on Russian judicial practice, international obligations, and human rights standards. Drawing on cases in which the author served as legal counsel, it highlights contradictions between the Russian Code of Administrative Offenses and the European Convention on Human Rights. The article examines the tension between public interest and the constitutional principle of proportionality, as well as criticism of Russian courts’ refusal to apply ECHR case law after the 2022 denunciation. It concludes with proposals for reforming Uzbekistan’s legislation based on doctrinal and comparative legal analysis